2004
DOI: 10.1128/aem.70.11.6363-6369.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Pasture Soil Microbial Community after Deposition of Cattle Urine Amended with [ 13 C]Urea

Abstract: Within grazed pastures, urine patches are hot spots of nitrogen turnover, since dietary N surpluses are excreted mainly as urea in the urine. This short-term experiment investigated 13 C uptake in microbial lipids after simulated deposition of cattle urine at 10.0 and 17.1 g of urea C m ؊2 . Confined field plots without or with cattle urine amendment were sampled after 4 and 14 days, and soil from 0-to 5-cm and 10-to 20-cm depths was analyzed for content and composition of phospholipid fatty acids (PLFAs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…The importance of urea as a N source for phytoplankton and bacteria has been well documented (Berman & Bronk 2003, Jørgensen 2006. However, the importance of urea as a C source is unclear, and has been studied rarely and with contradictory results (Petersen et al 2004, Jørgensen 2006. In the 1980s, investigators used radioactive 14 C labeled urea in parallel with 15 N labeled urea (Price & Harrison 1988 and references therein) to measure urea uptake, and an uncoupling between N and C uptake from urea was often found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of urea as a N source for phytoplankton and bacteria has been well documented (Berman & Bronk 2003, Jørgensen 2006. However, the importance of urea as a C source is unclear, and has been studied rarely and with contradictory results (Petersen et al 2004, Jørgensen 2006. In the 1980s, investigators used radioactive 14 C labeled urea in parallel with 15 N labeled urea (Price & Harrison 1988 and references therein) to measure urea uptake, and an uncoupling between N and C uptake from urea was often found.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dually labeled substrates is necessary to increase our insight into the role of DON cycling in pelagic ecosystems and to further our understanding of DON acquisition strategies by microbes. To take this relatively unexplored field of research one step further and study in detail which organisms are involved in the uptake of inorganic versus organic substrates, biomarkers such as PLFA (Boschker & Middelburg 2002, Petersen et al 2004) and D-alanine (Veuger et al 2005) can be valuable tools in combination with dually labeled substrates. Heterotrophs (bacteria) and photoautotrophs differ with respect to their uptake of C and N. Photoautotrophs can assimilate DIC during photosynthesis in the light and incorporate N throughout the entire day, resulting in a temporarily uncoupled uptake of C and N. Heterotrophs grow on organic substrates and usually take up C and N at the same time, but their relative use of C and N may differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of urea uptake in soils, a minor incorporation of 13 C from 13 C urea was detected in phospholipid fatty acids in both heterotrophic and nitrifying bacteria (Petersen et al 2004). It is uncertain if utilization of urea-C provides bacteria with nutritional advantages.…”
Section: Dfaa and Nhmentioning
confidence: 99%
“…Enhanced nitrification in response to grazing pressure has been reported in different unfertilized grassland ecosystems (Groffman et al, 1993;Frank et al, 2000;Le Roux et al, 2003;Patra et al, 2005). These changes can be explained by factors such as urine and dung input by herbivores (Ruess and McNaughton, 1987;Petersen et al, 2004) and changes in competition for N between microorganisms and plants (Busso et al, 2001;Hamilton and Frank, 2001). It has been further shown that grazinginduced differences in nitrification levels in grasslands are associated with changes in the abundance and community structure of ammonia-oxidizing bacteria (AOB) that were thought to be the key players of the first step of nitrification: oxidation of ammonia into nitrite (Patra et al, 2005(Patra et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%